Peran BAZNAS Dalam Pemberdayaan Ekonomi Santri Melalui Program Zmart Santripreneur - Azis, Ismi; Yolanda, Agnes; Khairunnisa, Arista (Politeknik Raflesia Press, 2024)
To increase the benefits of zakat in terms of economic empowerment, a zakat distribution program is needed that supports empowerment, namely not only consumptive but also productive. BAZNAS, in terms of economic empowerment of santri, distributes funds to help santri to become empowered and independent by holding an economic empowerment program through the zmart santripreneur program. This research was conducted on the Zmart Santriprenuer group of Bengkulu Province. This research uses a qualitative approach with a case study type. The data sources used are primary data and secondary data with data collection methods through interviews, observation and documentation. Data analysis techniques use data reduction, data presentation and drawing conclusions. The theory used in this research is the theory of the role of social workers proposed by Jim Ife, and the theory of empowerment outcome indicators according to Sumodiningrat. The aim of this research is to find out the role and results of the empowerment carried out by BAZNAS for students through the Zmart Program, especially Zmart students in Bengkulu Province . The BAZNAS institution is considered to be able to minimize poverty and thus empower students. Because in Islam, we are taught to share with each other in order to achieve prosperity. The research results show that the role of BAZNAS in empowering the students' economy has been carried out optimally. This is proven that BAZNAS has carried out its roles, namely the role as a social worker in economic empowerment for students who receive Zmart Santriprenuer assistance in Bengkulu Province through programs providing business capital assistance, training and group mentoring. Keywords: BAZNAS, Economic Empowerment, Zakat .